2017
DOI: 10.3390/ijerph14080887
|View full text |Cite
|
Sign up to set email alerts
|

Bullying Behaviors among Macanese Adolescents—Association with Psychosocial Variables

Abstract: Bullying is a widespread public health problem among school students. Using a large sample of Macanese school adolescents, the present study examines psychosocial conditions and demographic characteristics in discriminating the following four subgroups of students: victims; bullies; bully-victims; and a comparison group of adolescents. Participants included 2288 adolescents from 13 primary and secondary schools in Macau whose ages ranged from 10 to 20 years. Statistical results revealed significant differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 88 publications
5
32
1
3
Order By: Relevance
“…Furthermore, boys are more likely to be involved in bullying behaviors as most prior studies demonstrated [ 24 , 32 , 54 ]. Unlike other studies using samples from a small region [ 32 ], or other countries [ 55 ], our analysis indicates that being involved in bullying behaviors does not vary according to most of the family characteristics, such as the family structure, parents’ education and the socioeconomic status.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Furthermore, boys are more likely to be involved in bullying behaviors as most prior studies demonstrated [ 24 , 32 , 54 ]. Unlike other studies using samples from a small region [ 32 ], or other countries [ 55 ], our analysis indicates that being involved in bullying behaviors does not vary according to most of the family characteristics, such as the family structure, parents’ education and the socioeconomic status.…”
Section: Discussionmentioning
confidence: 98%
“…These differences of prevalence indicate the ambiguousness and uniqueness of the school bullying phenomena in Mainland China. Besides the studies from Hong Kong [ 20 ], Taiwan [ 21 , 22 ] and Macau [ 23 , 24 , 25 , 26 ], which are relatively different from Mainland China, most of the school bullying studies from Mainland China only used data from a small area, such as Beijing [ 27 ], Fujian [ 28 ], Guangdong [ 29 , 30 , 31 ], Xi’an [ 32 ], or unidentified central [ 33 ] or southwest China [ 34 ]. Two studies using national data were identified.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite lower prevalence, those who are pure victims or bully/victims in various regions in China suffer similar concurrent adverse mental health problems as have been reported in western countries, such as anxiety, depression, longlines, suicidality, and low life satisfaction (Cheng et al, 2010;Ji et al, 2003;Tang et al, 2018;Weng et al, 2017;Wu et al, 2015;Zhu & Chan, 2015). One longitudinal study in China further showed that victimization in primary school positively related to more internalizing symptoms six months later (Wang & Zhou, 2019).…”
Section: The Mental Health Status Of Bully Involvement In Chinamentioning
confidence: 82%
“…Based on the cross-cultural studies on bullying prevalence (Eslea et al, 2004;Xie et al, 2016;and Weight et al, 2015), we hypothesized that: (1) The prevalence of bullying would be lower in China than in Germany. Regarding the mental health consequence of bullying involvement, given that victims in China also reported mental health problems (e.g., Tang et al, 2018;Wang & Zhou, 2019;Weng et al, 2017;Wolke & Lereya, 2015), we expected that…”
Section: Aims and Hypothesesmentioning
confidence: 99%